Association of Epstein - Barr virus with Oral Squamous Cell Carcinoma and Oral Potentially Malignant Disorders - Sankari , S. Leena; Mahalakshmi , K.; Kumar, G. M. Kailash; Masthan, K. M. K.; Kumar, V. Naveen (Emerging Trends in Disease and Health Research Vol. 8, 2022)
Oral Squamous Cell Carcinoma (OSCC) has varied etiology. Genetic predisposition or the presence of oncogenic viruses are two etiological variables that might disrupt the physiological processes that limit cellular proliferation. The study was aimed to determine the association of Epstein- Barr virus (EBV) with oral squamous cell carcinoma and oral potentially malignant disorders (OPMD). The objective of the study was to quantify the EBV in oral exfoliated cells of OSCC and OPMD patients. Oral exfoliated cells were collected from the subjects diagnosed with OSCC (n=19), OPMD (n=23) and healthy subjects without any deleterious condition (n=39). The DNA extraction was performed with DNeasy Blood & Tissue Kits (Qiagen, Germany). Quantitative Real-Time PCR was then carried out with QuantiNova® SYBR® Green PCR Kit (Qiagen, Germany). Compared to healthy subjects, very high EBV load was observed in the oral exfoliated cells of OSCC and OPMD patients. The presence of EBV DNA in all three groups of individuals indicates that EBV is an oral resident. Aside from its presence, the high prevalence of EBV DNA in OSCC and OPMD shows a link between the two diseases. The elevated odds and risk ratio for EBV copy number point to a substantial link between this virus and OSCC and OPMD. This could be the first study to measure EBV DNA in OSCC and OPMD oral exfoliated epithelial cells.